Penerapan Nilai-nilai Keislaman dan Keindonesiaan di Sekolah Indonesia Den Haag (SIDH) Sebagai Pilar Pendidikan Karakter Islam - Khobli Arofad; Nadjma Laynufaria Almas; Ahmad Mushofihin; Veny Widiyanti Putri (Intelektual: Jurnal Pendidikan dan Studi Keislaman, 2020)
This study aims to describe how the application of Islamic and Indonesian values in the Hague Indonesian School (SIDH) as a pillar of Islamic character education. The method used in this research is to use qualitative approach, using descriptive type. The results showed that the application of Islamic and Indonesian values in the Hague Indonesian School (SIDH) was applied through learning activities, not only that, but also through other activities in the institution. These values can run of course with the help of educators or schools who are very enthusiastic in strengthening Islamic character education, especially in the Netherlands and Europe. With the Islamic and Indonesian values, it can make the character attached to the students in The Hague Indonesian School (SIDH).